Oxigenação hiperbárica melhora o controle redox e reduz a mortalidade na fase aguda do infarto do miocárdio em rato - Oliveira, Mario Sergio De [UNIFESP] (2021)
Introduction The potential of hyperbaric oxygenation to reduce cardiac lesions via redox homeostasis raises the possibility of extending the viability period of the at-risk myocardium. This circumstance is beneficial for late ischemic area reperfusion interventions. Aim The present study analyzed the changes in the redox system triggered by hyperbaric oxygenation therapy during acute myocardial infarction in rats. Material and methods Male Wistar EPM rats, weighing between 250 to 330 g (11-12 weeks of age) were used in the study. The rats (n = 138) were randomly separated into one of the following experimental groups: Sham (SH = 26), myocardial infarction (MI = 72), and infarction plus hyperbaric therapy (HBO = 40). The HBO therapy was carried out for 60 minutes on 2.5 absolute atmospheres. Heart samples were collected after 90 minutes of coronary occlusion and in a similar period for the SH group. Assays were performed to determine the total levels of superoxide dismutase, catalase, peroxiredoxin, and 3-nitrotyrosine proteins.Glutathione level was measured by indirect enzyme immunoassay. Superoxide anion was detected by the oxidation of dihydroethide on confocal microscopy. Nitrite and nitrate levels were evaluated by chemiluminiscence. Data are presented as mean + standard error of mean. Parametric data were analyzed with two-way ANOVA and Newman-Keuls post test. Kruskal-Wallis and Dunn’s post-test were applied to nonparametric data. The level of significance was set at p<0.05. Results Mortality was significantly higher in the MI group (37.5%) compared to the HBO group (15%). The infarction size was not significantly different between the HBO (38 ± 2.0%) and MI groups (43 ± 2.5%). Oxidized/reduced glutathione ratio (SH = 30+4; IM = 17+3; HBO = 10+1) and peroxiredoxin levels (SH = 1.45+0.26; MI = 1.24+0.18; HBO = 0.65+0.05; AU/ μg) were significantly higher in the SH and MI groups when compared to the HBO group. A significantly higher contente of superoxide dismutase (SH = xv 0.69+0.08; MI = 0.79+0.04; HBO = 1+0.06; AU/μg) and catalase (SH = 0.66+0.04; IM = 0.73+0.07; HBO = 0.97+0.06; AU/μg) was found in the HBO group compared to SH and MI groups. The 3-Nitrotyrosine (SH = 3.36+0.20; MI = 3.08+0.16; HBO = 2.40+0.18; AU) and superoxide radical (SH = 1.40+0.11; MI = 1.87+0.08; HBO = 0.86+0.08, AU) levels were significantly lower in the HBO group compared to the MI and SH groups. Conclusion The HBO therapy decreased mortality and improved redox control in the heart of rats in the acute phase of myocardial infarction.